New insight into cleaner control of heavy metal anode slime from aqueous sulfate electrolytes containing Mn (Ⅱ): Preliminary characterization and mechanism analysis. (10th March 2018) - Zhang, Chenmu; Jiang, Linhua; Xu, Fuyuan; Duan, Ning; Xin, Baoping; Han, Guimei; Zhang, Ge; Wen, Yucheng
Abstract: In this work the characterization and initial nucleation-growth mechanisms of the anode slime in aqueous sulfate electrolytes containing Mn 2+ were investigated in detail. Under laboratory conditions, this anode slime mainly consisted of manganese dioxides (in the form of α-MnO2 and γ-MnO2 ) with small amount of lead sulfate and oxides, determined by XRD, SEM and ICP-MS analysis. After the initial galvanostatic electrolysis, the results showed that the anode slime tended to generate onto the electrode surface at pH = 6.8 due to the rapid deposition of MnOOH solid intermediate, whereas more concentrated acid implied a positive role in favor of the generation of suspended anode slime via the diffusion of aqueous Mn 3+ . While deposited from a solution of 30 g/L Mn 2+ in 0.1 mol/L H2 SO4 onto a platinum substrate, the kinetic data was well described by progressive 3D nucleation model. Moreover, while deposited onto a lead-based anode surface, the kinetic data indicated to be close to follow the progressive 3D nucleation model whereas appeared the obvious deviation mainly due to the dissolution of the lead-based anode. While deposited at pH = 6.8, despite the corresponding nucleation-growth mechanism was observed to be unchanged, the most significant feature was the obvious appearance of the earlier onset of tmax as well as the larger response of current density from current–time transient curves attributed to the oxidation mechanism pathway preference of Mn 3+ intermediate. Considering the potential in controlling and reducing the generation of anode slime via a cleaner way, deepening the understanding of the initial nucleation-growth process of anode slime contributes to providing a feasible control method in manganese electrowinning process.